Correction: Enhancing carrier generation in TiO2 by a synergistic effect between plasmon resonance in Ag nanoparticles and optical interference. Issue 48 (25th November 2015) - Cacciato, Giuseppe; Bayle, Maxime; Pugliara, Alessandro; Bonafos, Caroline; Zimbone, Massimo; Privitera, Vittorio; Grimaldi, Maria Grazia; Carles, Robert
Abstract : Correction for 'Enhancing carrier generation in TiO2 by a synergistic effect between plasmon resonance in Ag nanoparticles and optical interference' by Giuseppe Cacciato et al., Nanoscale, 2015, 7, 13468–13476.